2008
DOI: 10.1104/pp.108.123778
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Type of Thioredoxin Dedicated to Symbiosis in Legumes  

Abstract: Thioredoxins (Trxs) constitute a family of small proteins in plants. This family has been extensively characterized in Arabidopsis (Arabidopsis thaliana), which contains six different Trx types: f, m, x, and y in chloroplasts, o in mitochondria, and h mainly in cytosol. A detailed study of this family in the model legume Medicago truncatula, realized here, has established the existence of two isoforms that do not belong to any of the types previously described. As no possible orthologs were further found in ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
45
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 45 publications
2
45
0
Order By: Relevance
“…Plants contain several nuclear genes encoding Trx proteins (Gelhaye et al, 2005). In Arabidopsis (Arabidopsis thaliana), at least 20 Trx genes have been reported (Meyer et al, 2002), classified into six families, Trx f, Trx h, Trx o, Trx m, Trx x, and Trx y, and a novel Trx s, recently described in Medicago truncatula that expands this family of proteins in legumes (Alkhalfioui et al, 2008). The subcellular location of the different Trxs showed that the chloroplast contains Trx f, m, x, and y and the atypical form CDSP32 (Collin et al, 2003).…”
mentioning
confidence: 99%
“…Plants contain several nuclear genes encoding Trx proteins (Gelhaye et al, 2005). In Arabidopsis (Arabidopsis thaliana), at least 20 Trx genes have been reported (Meyer et al, 2002), classified into six families, Trx f, Trx h, Trx o, Trx m, Trx x, and Trx y, and a novel Trx s, recently described in Medicago truncatula that expands this family of proteins in legumes (Alkhalfioui et al, 2008). The subcellular location of the different Trxs showed that the chloroplast contains Trx f, m, x, and y and the atypical form CDSP32 (Collin et al, 2003).…”
mentioning
confidence: 99%
“…Knowledge of the redox regulatory network of nodules is only slowly emerging and is still in a fragmentary state. In pea (Pisum sativum), the content of PrxIIF in nodules is similar to that in roots and remains constant during nodule development (Groten et al, 2006), whereas in soybean (Glycine max), a Trxh isoform is essential for nodulation (Lee et al, 2005), and in M. truncatula, two isoforms of a new type of Trx, designated Trxs ("s" for symbiosis), are highly expressed in nodules (Alkhalfioui et al, 2008).…”
mentioning
confidence: 99%
“…The Arabidopsis cytosolic system consists of eight different Trx h and two homodimeric NADPH-dependent thioredoxin reductases (NTR, EC 1.6.4.5) (Laloi et al 2001;Meyer et al 2002), while the mitochondrial and nuclei ones include a Trx o and NTR (Laloi et al 2001;Martıé t al. 2009) and endoplasmic reticulum contain a Trx s (Alkhalfioui et al 2008). However, the chloroplastic Trx system is even more complex than the cytosolic one.…”
Section: Introductionmentioning
confidence: 99%